Sarcopenia and sarcopenic obesity in patients with muscular dystrophy - Luciano eMerlini; Alessandro eVagheggini; Daniela eCocchi (Frontiers in Aging Neuroscience, 2014)
Aging sarcopenia and muscular dystrophy are two conditions characterized by lower skeletal muscle quantity, lower muscle strength, and lower physical performance. Aging is associated with a peculiar alteration in body composition called sarcopenic obesity characterized by a decrease in lean body mass and increase in fat mass. To evaluate the presence of sarcopenia and obesity in a cohort of adult patients with muscular dystrophy we have used the measurement techniques considered golden standard for sarcopenia that is for muscle mass dual energy X-ray absorptiometry (DXA), for muscle strength hand held dynamometry, and for physical performance gait speed. The study involved 14 adult patients with different types of muscular dystrophy. We were able to demonstrate that all patient were sarcopenic-obese. We showed in fact that all were sarcopenic based on appendicular lean, fat & bone free, mass index (ALMI). In addition all resulted obese according to the % of body fat determined by DXA in contrast with their body mass index ranging from underweight to obese. Skeletal muscle mass determined by DXA was markedly reduced in all patients and correlated with residual muscle strength determined by hand held dynamometry, and physical performances determined by gait speed and respiratory function. Finally we showed that ALMI was the best linear explicator of muscle strength and physical function. Altogether, our study suggest the relevance of a proper evaluation of body composition in muscular dystrophy and we propose to use, both in research and practice, the measurement techniques that has already been demonstrated effective in aging sarcopenia.